Burnout Syndrome in public school teachers in Sorocaba, São Paulo, Brazil - Souza, Maíra Cazeto Lopes de; Lucca, Sérgio Roberto de (HSJ, 2021)
Objective: To identify the prevalence of Burnout Syndrome (BS) in a sample of 107 elementary school teachers (cycle II and high school) in Sorocaba/SP and analyze possible associations of psychosocial and organizational factors at work with the dimensions of burnout. Methods: Cross-sectional epidemiological study, conducted through a selection of a convenience sample, which included 107 teachers from state schools in Sorocaba using the following criteria: having entered the public teaching career for at least one year and working predominantly as a teacher, that is, not having more hours in administrative positions. Data collection was conducted in eight schools in the city, and two forms were used, the “Maslach Burnout Inventarie-Educators Survey” (MBI-ES) and a biopsychosocial form. Pearson's chi-square test and logistic regression analysis were performed for data analysis, adopting a significance level of 5%. Results: There was a prevalence of BS in 4.7% of teachers, with 29% of teachers showing high Emotional Exhaustion, 33.6% high Depersonalization and 18.7% low Professional Fulfillment. Positive associations were found between factors such as lack of recognition, dissatisfaction with work and situations of harassment with the dimensions of the BS. Conclusion: The results suggest a warning sign for illness characterized by burnout in the sample of teachers studied.